Meningkatkan Keterampilan Bercerita dengan Menggunakan Media Gambar Berseri dalam Pembelajaran Bahasa Indonesia Murid Kelas III Sd Negeri 37 Turungan - Ira Irviana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Abstract: This research aims to determine the ability to tell stories using series of picture media in Indonesian language learning for class III students at SD Negeri 37 Turungan. This type of research uses Classroom Action Research (PTK) which consists of four stages, namely; planning, implementation, observation, and reflection. The focus of this research has two focus points, namely the dependent variable and the independent variable, where the independent variable is serial image media in Indonesian language learning and the dependent variable is storytelling skills with the research subjects being teachers and students with a total of 11 students consisting of 9 men and 2 women. . The data collection analysis technique used is qualitative analysis, namely through observation of teacher and student activities, tests and documentation, teacher activities in cycle I are in the good category, in cycle II in the good category and in cycle III they are in the good category. Student activities in cycle I were in the sufficient category, in cycle II were in the good category, in cycle III were in the good category. The results of storytelling skills in the first cycle were in the very poor category, then the second cycle was carried out in the very good category and in the third cycle the results of the storytelling skills had reached 100% or were in the very good category. The conclusion of this research is that by implementing a learning model using serial image media, it can improve storytelling skills in the Indonesian language learning subject for class III students at SD Negeri 37 Turungan.